Optimasi Persediaan untuk Ketersediaan Perkakas Kerja di Bengkel Otomotif - Hariyo P. S. Pratomo; Ivan Christian Hernando; Matthew Jeffrey Rudijanto; Joseph Wicaksono Tandio (CV. IRA PUBLISHING, 2025)
Automotive workshops commonly face inefficiencies in special-tool availability due to manual and non-transparent tracking systems. This study addresses this challenge by examining the impact of limited tool quantities on operational performance, particularly the low average service level (86.18% vs. the 95% target). This study is among the first to integrate a digital tool management system with quantitative inventory-optimization methods, i.e., Safety Stock and Cost-Benefit Analysis (CBA), in an automotive workshop context. Borrowing-transaction records collected over 60 days were analyzed to identify critical tools with the highest demand variability. Although most tools achieved full availability, 15 high-demand tools contributed to reduced overall service level and were therefore prioritized in the optimization process. Application of Safety Stock analysis recommended ideal inventory quantities, while CBA revealed diminishing-return thresholds, preventing unnecessary investment. Key improvements include increasing service level from 71.27% to 99.51% and enhancing cost efficiency to 89.04%. The combined digital recording system and quantitative optimization framework have proved highly effective in improving tool availability and reducing operational costs. This approach offers a scalable model for automotive workshops seeking to enhance efficiency and sustainability through data-driven tool-management strategies.